First nosocomial outbreak of vanA-type vancomycin-resistant Enterococcus raffinosus in France. Issue 4 (December 2016) - Jolivet, S.; Fines-Guyon, M.; Nebbad, B.; Merle, J.C.; Le Pluart, D.; Brun-Buisson, C.; Decousser, J-W.; Cattoir, V.
Summary: Background: Vancomycin-resistant Enterococcus raffinosus has rarely been associated with nosocomial infection and outbreaks. Aim: To report the successful control of a nosocomial outbreak of vanA -type vancomycin-resistant E. raffinosus in a surgical intensive care unit. Methods: The investigation of the outbreak is reported with control measures taken. Molecular typing of vancomycin-resistant E. raffinosus isolates was performed by repetitive sequence-based polymerase chain reaction (PCR). Findings: Between September and October 2014, vancomycin-resistant E. raffinosus isolates were isolated from four patients. The index patient had been hospitalized previously in Portugal, and was not found to be colonized by vancomycin-resistant enterococci on screening cultures obtained at admission. However, vancomycin-resistant E. raffinosus was isolated from a bile sample 19 days after hospital admission. All four isolates were resistant to both vancomycin and teicoplanin due to the presence of the vanA gene, while remaining susceptible to daptomycin and linezolid. Repetitive sequence-based PCR confirmed the spread of a single vanA -positive E. raffinosus clone. Infection control measures including direct PCR screening on rectal specimens, contact precautions, and cohorting of patients and personnel led to successful control of the outbreak. Conclusion: This is the first reported outbreak of vanA -type vancomycin-resistant E. raffinosus in France in both clinical and screening specimens among hospitalized patients. The inability of routine selective screening media to detect the vancomycin-resistant E. raffinosus in the index case likely contributed to the outbreak.